Fecal microbiome transplant from patients with lactation mastitis promotes mastitis in conventional lactating mice - Kong, Chao-Yue; Yang, Yi-Qin; Han, Bing; Chen, Hui-Ling; Mao, Yu-Qin; Huang, Jia-Ting; Wang, Li-Shun; Li, Zhan-Ming (Frontiers in Microbiology, 2023)
Lactation mastitis seriously affects the health of lactating females and infants. However, the etiology of clinical lactation mastitis remains unclear. Here, using microbiota-humanized mice as a model, we showed that the gut microbiota of lactation mastitis patients alone could lead to mastitis. We compared the fecal microbiota of lactation mastitis and normal females. We used fecal microbiota transplantation (FMT) in an antibiotic-pretreated mouse model to test whether gut microbes contribute to human lactation mastitis. Gut microbiota diversity was reduced and dysbiosis in lactating mastitis patients. FMT from lactation mastitis (M-FMT), but not healthy person (H-FMT), to antibiotic-treated mice resulted in lactation mastitis. Inflammation in mice caused by gut microbiota in lactating mastitis patients appears to be pervasive. Hepatocytes from mice that received feces from lactating mastitis showed marked swelling. In addition, serum pro-inflammatory factors IL-4, IL-17, MPO, IL-6, IL-1β and TNF-α were significantly increased in the M-FMT group. The Firmicutes/Bacteroidetes ratio (F/B), a biomarker of gut dysbiosis, was significantly increased in the M-FMT group. At the phylum level, Actinobacteria significantly increased, and Verrucomicrobia significantly decreased in the M-FMT group. At the genus level, Ruminococcus and Faecalibacterium were significantly reduced, while the Parabacteroides were significantly increased, in the fecal of both patients with lactation mastitis and M-FMT mice. Furthermore, there was an "amplification effect" on microbiota differences and mastitis disease following human-to-mouse FMT. This study shows that the gut microbiota in lactating mastitis patients is dysbiosis and contributes to the pathogenesis of mastitis.